DFT, Molecular Docking, Bioactivity and ADME Analyses of Vic-dioxim Ligand Containing Hydrazone Group and its Zn(II) Complex - Gökçe Çalişkan, Şerife (Current Computer - Aided Drug Design, 2024)
Background: Cancer is one of the diseases affecting a large population worldwide and resulting in death. Finding new anti-cancer drugs that are target-focused and have low toxicity is of great importance. Objective: This study aimed to investigate the effects of vic-dioxime derivatives carrying hydrazone group and its Zn(II) complex on cancer using molecular docking, bioactivity and quantum chemical calculations. Methods: Molecular docking studies were performed on epidermal growth factor receptor and vascular endothelial growth factor receptor 2 target proteins. Furthermore, molecular geometry was performed, and the frontier molecular orbitals, Mulliken charges and molecular electron density distribution were evaluated using density functional theory. Also, the bioactivity parameters of the compounds were evaluated, and ADME analysis was performed using web-based tools. Results: Higher binding affinity was observed for Zn(II) complex with target proteins vascular endothelial growth factor receptor 2 and against epidermal growth factor receptor when compared with LH2. Only the Zn(II) complex against the epidermal growth factor receptor had ligand efficiency and fit quality in the valid range. Furthermore, LH2 has the most potent electrophilic ability (acceptor) among other compounds. Moreover, both LH2 and Zn(II) complexes strongly satisfy Lipinski’s rule of five. Conclusion: In conclusion, these novel compounds, especially Zn(II) complex, can be new candidates for anticancer drug development studies which are target-focused and have low toxicity.
Keywords: ADME analysis